PEMANFAATAN PLTA SKALA PICO SEBAGAI SOLUSI PENERANGAN UNTUK BUDIDAYA IKAN AIR TAWAR DI PEKON NEGERI SAKTI KECAMATAN GEDONG TATAAN, KABUPATEN PESAWARAN - Harmen Harmen; Ahmad Yonanda; Amrizal Amrizal (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2022)
Pekon Negeri Sakti, Gedong Tataan District has a location close to the flow of rivers with a small discharge and has been used by some residents to become fish farming ponds. So far, the problem is the lack of lighting for fish ponds and the large number of illegal fishing in the local area at night. Problems faced by Partners can be overcome by looking at the potential of natural resources at partner locations. Judging from the potential of natural resources in the location, there is a river flow that can be used as a pico-hydro power plant or pico scale PLTA. The general goal of this service is to implement appropriate technology in areas near river flows as a source of electricity. The manufacture of microhydro power plants starts from measuring the potential of water, designing turbines and generators, then observing the working system and estimating the electrical power that will be generated. From the survey results, it is known that the water discharge is 2 liters/second and has a fall height or head of 0.5 m. The manufacture of pico-hydro power plant using a screw turbine is capable of producing 5 watts of electrical power. The power generated can be useful for residents for continuous lighting around the pond and at the same time to overcome the potential for illegal fishing at night.